The biomechanics of frontal and lateral collision - Kallieris, Dimitrios (Human biomechanics and injury prevention, 2000)
Frontal collisions with instrumented and with restraint systems (belt, force limiter, air bag) protected cadavers at impact velocities of 47-55 km/h and average sled decelerations of 10-20 g will be reported.